Dietary Care Lots of Vegetables in Weight Loss Obesity Women of Reproductive Age - Sitti Sahariah Rowa; Hikmawati Mas'ud (Poltekkes Kemenkes Palu, 2023)
Obesity is one of the issues contributing to the rise of non-communicable diseases such as hypertension and stroke. One of the preventive measures against obesity is the consumption of vegetables and fruits high in fiber, which is used as a strategy for weight reduction. This study aims to establish a dietary care model for reducing weight and blood lipid levels in obese Women of Reproductive Age (WRA). The research was conducted in the urban area of Makassar, specifically in the Berua sub-district, and in the suburban area of Untia sub-district, Biringkanaya district, Makassar city. The research follows a quasi-experimental design known as the 'Non-Equivalent Control Group Pretest-Posttest Design.' Data analysis utilized paired t-tests conducted before and after a 2-month education period using flipcharts and examples of vegetable portions. The research findings revealed that there were 39 samples in obesity category 1 and 21 samples in obesity category 2. Regarding risk factors, there was a significant change in knowledge (p = 0.000). The average weight of the samples decreased by 1.8 kg after a 2-month education period, with a significant effect (p = 0.000). Protein intake showed no significant impact based on statistical tests, whereas energy, fat, and carbohydrate intake demonstrated significant effects, particularly with a 300g intake of vegetables and the most common energy range being 1750-2077 kcal.The proposed model design suggests that consuming 4 portions of vegetables and a total of 1750 kcal can lead to a weight reduction of 1.8 kg over a 2-month period.